Evaluation of horizontal distance between WALA-FA point in angle's Class I, Class II, and Class III malocclusion - R Mahalakshmi; MM Varadharaja; Reshmi Leila Ninan; V Vignesh Kumar; B Kanagasabapathy; M.D Saravana Balaji (Wolters Kluwer Medknow Publications, 2021)
Introduction: The objective of the study was to measure the horizontal distance between the FA-WALA (Facial Axis Point-William Andrews and Larry Andrews) of posterior teeth in Angle's Class I, Class II, and Class III malocclusions and to assess the depth of the Curve of Spee, to find the correlation between intercanine FA and intercanine WALA and its significance. Material and Methods: Sixty pretreatment mandibular casts of patients with an age range of 18-35 years were included. A sample size of 20 was evaluated in Angle's Class I, Class II, and Class III, respectively. The WALA ridge and FA points were marked in the model and calibrated using the digital Vernier caliper. Results: There was an incremental increase in the horizontal distance from the FA-WALA in the posterior teeth. The mandibular intercanine FA-FA and intercanine WALA-WALA distance were greater in Angle's Class III group when compared to Angle's Class II. The Curve of Spee measurement was increased in Angle's Class II group, while Angle's Class III had a flat curve. Conclusion: The horizontal distance between FA-WALA increased incrementally in the posterior teeth in Angle's Class I, Class II, and Class III malocclusions. In Angle's Class II malocclusion, the Curve of Spee measurement was increased and had a narrower mandibular arch.